FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU BUANG AIR BESAR PADA MASYARAKAT DI DESA BANDAR BATAUGA KECAMATAN BATAUGA KABUPATEN BUTON SELATAN - Anna Dwiana; Lucky Herawaty (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Determinants of defecation behavior among coastal community in district of South ButonPurposeThe purpose of this study was to identify the factors associated with community attitudes toward defecation in Bandar Batauga village Batauga district South Buton Regency.MethodsThis study used mixed methods, with convergent/concurrent design to merge the results of the quantitative and qualitative data analysis, their combination and contributions to the problem from multiple angles and multiple perspectives. The total number of respondents for this study were 110, divided into 100 respondents and 10 informants.ResultsChi-square analysis showed associated knowledge p-value = 0.0117; PR = 0.635 and facility availability p-value = 0.0002; PR = 1.876 with open defecation behavior.ConclusionTo improve the cooperation between health workers, heads of the environment, and communities need to provide more health education in order to increase the knowledge of the community and support the program of toilet procurement to support basic sanitation facilities.